2013
DOI: 10.1186/1471-2180-13-266
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli YmdB regulates biofilm formation independently of its role as an RNase III modulator

Abstract: BackgroundRibonuclease III (RNase III) activity modulates hundreds of genes in Escherichia coli (E. coli). YmdB, a member of the macrodomain protein family, is one of known trans-acting regulators of RNase III activity; however, the significance of its regulatory role in specific bacterial cellular processes and related genes has not been determined. YmdB overexpression was used to model YmdB-induced RNase III inhibition in vivo, and microarray analysis identified gene targets and cellular processes related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…Protein mono-ADP-ribosylation is predictably more common in bacteria (10), where homologues of MacroD proteins are the most abundant representatives. Macrodomain protein YmdB from Escherichia coli seems to be a multifunctional protein that regulates RNase III activity and modulates bacterial biofilm formation (40). …”
Section: Discussionmentioning
confidence: 99%
“…Protein mono-ADP-ribosylation is predictably more common in bacteria (10), where homologues of MacroD proteins are the most abundant representatives. Macrodomain protein YmdB from Escherichia coli seems to be a multifunctional protein that regulates RNase III activity and modulates bacterial biofilm formation (40). …”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, YmdB interacts with the ribonuclease RNase III and acts as a negative regulator of its cleavage activity (Kim et al 2008;Paudyal et al 2015). Furthermore, YmdB was suggested as a regulator of gene expression both through RNase III regulation as well as in an RNase III-independent manner, thereby influencing biofilm formation and antimicrobial resistance (Kim et al 2013(Kim et al , 2017. While it was shown that YmdB is catalytically active Zhang et al 2015b), the role of this activity in vivo remains elusive.…”
Section: Viral and Microbial Macrodsmentioning
confidence: 99%
“…SCO6450 orthologues are found in most of the bacteria . Escherichia coli homologue YmdB appears to be a multifunctional protein that regulates variety of cellular processes; deacetylates O AADPr, hydrolyses MARylated protein substrates, regulates RNAse III activity and modulates bacterial biofilm formation .…”
Section: Adp‐ribosylation In Bacteriamentioning
confidence: 99%